2020
DOI: 10.1177/1747954120919909
|View full text |Cite
|
Sign up to set email alerts
|

Is training age predictive of physiological performance changes in developmental rugby league players? A prospective longitudinal study

Abstract: The aim of this study was to determine if training age – rugby league training age, resistance training age and cardiovascular training age – was predictive of changes in physiological performance in developmental rugby league players. Developmental rugby league players from one elite club ( n = 147, mean age = 15.8 ± 1.1 years) playing at Under 16 and Under 18 representative levels were tracked longitudinally over two consecutive seasons. Estimated aerobic capacity, jump height, upper body strength endurance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Six articles also reported a range of participant observations of three or more [ 34 , 36 , 47 , 51 , 65 , 67 ]. The remaining articles either confirmed that all participants were observed at all time points [ 13 , 28 , 30 , 33 , 35 , 46 , 56 , 58 , 59 , 64 , 66 ], or the number of participant observations was not stated [ 29 , 31 , 32 , 37 , 42 , 48 , 49 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Six articles also reported a range of participant observations of three or more [ 34 , 36 , 47 , 51 , 65 , 67 ]. The remaining articles either confirmed that all participants were observed at all time points [ 13 , 28 , 30 , 33 , 35 , 46 , 56 , 58 , 59 , 64 , 66 ], or the number of participant observations was not stated [ 29 , 31 , 32 , 37 , 42 , 48 , 49 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other reasons included within and between season differences, comparison of sub-groups over time [ 39 ], non-normal data [ 30 ] and longitudinal design [ 28 ]. Methods for supporting the justification included referencing a journal article ( n = 14; 35%) [ 29 , 31 34 , 42 , 46 , 47 , 51 , 52 , 61 63 , 65 ], the MLwiN software ( n = 5; 13%) [ 36 , 38 , 44 , 45 , 63 ], books ( n = 2) [ 28 , 54 ] and Hopkins website ( n = 1) [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations